2009
DOI: 10.1212/wnl.0b013e3181c55d17
|View full text |Cite
|
Sign up to set email alerts
|

EEG-fMRI

Abstract: Our study provides different types of support (topography, concordance with PET and SPECT, structural peculiarities, postoperative histology) that EEG-fMRI may help to delineate the epileptic focus in patients with nonlesional frontal lobe epilepsy, a challenging group in the preoperative evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
110
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(117 citation statements)
references
References 26 publications
6
110
0
1
Order By: Relevance
“…Combined EEG‐fMRI usually markedly improves the fMRI mapping of the epileptic activity (Moeller et al., 2009), with the requirement of the activity to be present during the multimodal scanning. However, our patients did not exhibit epileptic activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Combined EEG‐fMRI usually markedly improves the fMRI mapping of the epileptic activity (Moeller et al., 2009), with the requirement of the activity to be present during the multimodal scanning. However, our patients did not exhibit epileptic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the pulsation abnormalities could be linked to the detected abnormalities in neurovascular coupling in epilepsy, where an abnormal and prolonged dilation in the blood vessels are detected prior to epileptiform activity (Jacobs et al., 2009; Mäkiranta et al., 2005; Moeller et al., 2009; Osharina, Aarabi, Manoochehri, Mahmoudzadeh, & Wallois, 2017). Prolonged vasodilatations may minimize glymphatic pulsation of the perivascular CSF reservoir and lead to altered tissue homeostasis and further to epileptic activity (Jessen et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…EEG/fMRI may help in the evaluation of patients who are candidates for surgery 6 and, in patients with nonlesional frontal lobe epilepsy, EEG/fMRI contributed to localize foci subsequently confirmed by other imaging modalities or pathology. 7 Finally, in a postsurgical population, it was shown that when the resection included the BOLD activation region, patients showed good outcome.…”
mentioning
confidence: 99%
“…It is now possible to delineate structural and functional information of the part of the brain that causes seizures in patients with epilepsy disorder by combining EEG, MRI, and fMRI findings [11,19,20]. They can help to better localize the focus [21][22][23][24]. Hence, we decided to integrate EEG recordings, MRI, and fMRI in the proposed system as multimodal imaging parameters.…”
Section: The Content Of Multimodalitymentioning
confidence: 99%